Antimicrobial peptides from free-range chicken egg white prepared ultrasound - SILVA, Edson Flávio Teixeira da; SANTOS, Wellington; FALCÃO, Rosângela Estevão Alves; NASCIMENTO, Talita Camila; SANTOS-DONADO, Priscila; GOMES, José Erick Galindo; PESSOA, Adalberto; MOREIRA, Keila (Food Science and Technology, 2025)
Antimicrobial peptides are biomolecules that have great potential for pharmaceutical application, as they are considered to be natural alternatives for combating multi-resistant agents to traditionally marketed drugs. The objective of this research was to prospect for new antimicrobial peptides obtained from free-range egg white proteins that had been pre-treated by ultrasonic sonication, and subjected to the hydrolytic action of commercial trypsin. The maximum percentage of 25.90% proteolysis was found from the application of sonication pre-treatment of egg white for 16 minutes and 29 seconds, followed by enzymatic hydrolysis for 128 minutes and 35 seconds. The peptides (< 3 kDa) were evaluated for their antimicrobial action against six bacterial strains. These tests presented a minimum inhibitory concentration of 1.56 mg.mL–1 for the strains Bacillus cereus ATCC 11778, Enterococcus faecalis ATCC 29212, and Salmonella typhimurium 31194; while for the strains Listeria monocytogenes ATCC 19117, Escherichia coli ATCC 25922, and Serratia marcescens ATCC 13880 the value of minimum bactericidal concentration was 0.78 mg.mL–1. Furthermore, a minimum bactericidal concentration of 0.78 mg.mL–1 was observed for all strains, being considered equivalent to the minimum inhibitory concentration. The study of cell death kinetics revealed excellent antimicrobial action in less than 120 minutes for all bacterial strains evaluated. 10 were identified and considered significant for the present study. These characteristics have not yet been reported in scientific studies, nor are they present in databases related to proteins and peptides. Given these results, this protein substrate has a high potential for use in the prospecting of antimicrobial products.